Formation of Japan’s image in Central Asia (Journal of Oriental Studies, 2017)
At the present time, it is possible to observe the dynamic rates of developmentof the relationship between Japan and the countries of CentralAsia. And this concerns the political, diplomatic, trade and economic, culturaland educational spheres of cooperation between the parties. Japanesecompanies are actively investing in various sectors of economic andeconomic development, еspecially in the sphere of reconnaissance andextraction of natural resources and energy. At the same time, it is importantto keep in mind the rich and advanced experience of Japan in the field ofmodern technologies and the development of human resources, the studyand use of which will be of great benefit in the further development of thecountries of Central Asia. Between Japan and the countries of Central Asiathere are no major contradictions and problems of a fundamental nature.Nothing hinders active mutual cooperation. apan has a positive image anda high degree of confidence in this region. This article examines Japan’spolicy in Central Asia, which contributed to the formation of a positiveimage of Japan.